2018
DOI: 10.1007/s40737-018-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

How Young Adults in London Experience the Clubhouse Model of Mental Health Recovery: A Thematic Analysis

Abstract: Clubhouses are recovery orientated, participatory communities in which people with mental health diagnoses can take part in the running of the clubhouse. The objective of this research was to produce the first qualitative study of its kind, examining how the clubhouse model of mental health recovery is perceived and experienced by young adults aged 16-25. Five participants provided lengthy and detailed semi-structured interviews regarding their experiences as members of a clubhouse in London. Analysis produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 28 publications
(35 reference statements)
3
16
0
Order By: Relevance
“…A strong sense of demotivation seemed to dominate participants' lives, which admittedly changed for the better after they joined the Clubhouse. In line with previous research (Kinn et al, 2018;Norman, 2006;Pardi & Willis, 2018;Roth, 2017), we found that individuals gained several positive life experiences after becoming a member at a Clubhouse, so their range of available RRs have increased.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A strong sense of demotivation seemed to dominate participants' lives, which admittedly changed for the better after they joined the Clubhouse. In line with previous research (Kinn et al, 2018;Norman, 2006;Pardi & Willis, 2018;Roth, 2017), we found that individuals gained several positive life experiences after becoming a member at a Clubhouse, so their range of available RRs have increased.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the results of this study correspond with those of previous international research in the field (Biegel et al, 2013;Jung & Kim, 2012;Norman, 2006;Pardi & Willis, 2018;Roth, 2017;Tanaka et al, 2015;Tanaka & Davidson, 2015a, 2015b, suggesting that being a Clubhouse member is a similar experience across countries, social systems, and cultures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The 19 studies included in this review came from 5 different countries; 8 studies came from the UK [21,22,[25][26][27][28][29][30], 5 from the US [31][32][33][34][35], 3 from Australia [36][37][38], 2 from Canada [39,40] and 1 from Denmark [41]. Eight studies utilised a qualitative methodology [25,28,29,34,[36][37][38]40] and two studies were based on a qualitative case-study approach [22,33]. In contrast, three studies followed a quantitative descriptive approach [30,35,39], while one study had a mixed-methods design [26].…”
Section: Study Characteristicsmentioning
confidence: 99%